EUFEMED London Conference 2017: Exploratory Medicines Development: Innovation and Risk Management - Van Bortel, Luc; Sourgens, Hildegard; Breithaupt-Grögler, Kerstin; Caplain, Henri; Donazzolo, Yves; Klingmann, Ingrid; Hammond, Michael; Hardman, Timothy C.; Stringer, Steffan; de Hoon, Jan (Frontiers in Pharmacology, 2018)
The first formal conference of the EUropean Federation for Exploratory MEdicines Development (EUFEMED) held in London was the result of a collaborative effort of its founding associations: the Association for Applied Human Pharmacology (AGAH; Germany), the Association for Human Pharmacology in the Pharmaceutical Industry (AHPPI; UK), the Belgian Association of Phase-I Units (BAPU; Belgium), and Club Phase-I (France). The conference focused on innovation and risk management in early clinical drug development. Among other innovations, immunotherapy in oncology and inflammatory diseases were discussed as well as the importance of adaptive trial designs in early clinical drug development. Consideration was given to assessing and mitigating risk in early clinical drug development, and included a preconference workshop. Different measures to minimize risks in healthy volunteers and patients in first-in-human trials were discussed in addition to the importance of non-clinical data, the need for reliable biomarkers, improved communication on adverse events (AEs) and well-trained study sites with ready access to intensive care units and clinical specialists. The need for a European-wide system for prevention of over-volunteering was also discussed. The conference provided opportunity to discuss these developments and concerns and the changing regulatory environment with stakeholders from academia, industry, and regulatory agencies including the European Medicines Agency (EMA). Presentations given by invited speakers are published on http://www.eufemed.eu/london-conference-2017/.